Myasthenia gravis as a presenting feature in a patient with SCLC: A case report (Bangladesh Journal of Neuroscience, 2015)
Small cell lung cancer (SCLC) is the most frequent cancer histology associated with paraneoplastic syndromes. These syndromes are typically caused by ectopic hormone production or immune-mediated tissue destruction caused by neural antigen expression from cancer cells. Lambert-Eaton myasthenic syndrome is well known to be a classical paraneoplastic syndrome of small cell lung carcinoma (SCLC).Only a few cases of myasthenia gravis (MG) and SCLC were previously reported. The causal association between lung cancer and non-thymomatous myasthenia gravis has not been clarified yet. To date, there has been no evidence supporting the speculation that association of myasthenia gravis with lung cancer might be one of the phenotypes of paraneoplastic syndrome. We present a case of a 47-year-old male ex-smoker with SCLC associated with myasthenia gravis evidenced by the clinical findings of ptosis, dysphagia, proximal weakness, and positive repetitive nerve stimulation (RNS) test.Bangladesh Journal of Neuroscience 2015; Vol. 31 (1): 50-55